Exploring strategies to manage expectational knowledge in higher education after COVID-19 pandemic - Sunarsi, Denok; Djulius, Horas; Affandi, Azhar; Priadana, M. Sidik; Narimawati, Umi; Sudirman, Iman (Journal of Education and Learning (EduLearn), 2025)
The COVID-19 pandemic has brought unprecedented challenges and opportunities for knowledge management systems (KMS) in various domains and sectors. This research explores the strategies to manage expectational knowledge in higher education after the COVID-19 pandemic. This study employed a qualitative research method with a case study design to capture the students’ perspectives on strategies to manage expectational knowledge in higher education after the COVID-19 pandemic. The participants are students at the doctoral program, Universitas Pasundan, Bandung, West Java, Indonesia. The interview was conducted in December 2022 using a semi-structured interview technique and then was analyzed using thematic analysis. This research found four strategies doctoral management students use to manage expectation knowledge after the COVID-19 pandemic. The strategies are codification, personalization, knowledge partnering, and knowledge harvesting. The research implications of this study provide a foundation for future research endeavors to advance the understanding and application of knowledge management strategies in the post-pandemic higher education landscape.